The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/tax.12451
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the Mammilloid clade (Cactaceae) resolves the monophyly of Mammillaria

Abstract: To resolve more than 150 years of taxonomic confusion regarding the genus Mammillaria, the molecular phylogeny of the Mammilloid clade, including the genera Cochemiea, Coryphantha, Cumarinia, Escobaria, Mammillaria, Neolloydia, and Ortegocactus, is reconstructed. We included broad sampling of genera as well as a regionally nearly complete taxon sampling of Mammillaria and Cochemiea from the Baja California region. Employing the large single-copy region of the plastid genome as sequence data, we conducted maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 47 publications
3
37
1
Order By: Relevance
“…However, it has been proposed that Mammillaria is a polyphyletic group. Breslin et al (2021), using plastid genomes, confirmed previous studies showing Mammillaria is nonmonophyletic, as currently circumscribed, so they proposed that the Mammilloid clade be circumscribed in three monophyletic genera, Mammillaria s.s., Coryphantha and Cochemiea s.l., as previously suggested by Vázquez- Sánchez et al (2013). Furthermore, the taxonomy of Mammillaria has historically been difficult due to large morphological variability, phenotypic plasticity, sympatric distribution of species, and suspected hybridization events.…”
Section: Introductionsupporting
confidence: 76%
“…However, it has been proposed that Mammillaria is a polyphyletic group. Breslin et al (2021), using plastid genomes, confirmed previous studies showing Mammillaria is nonmonophyletic, as currently circumscribed, so they proposed that the Mammilloid clade be circumscribed in three monophyletic genera, Mammillaria s.s., Coryphantha and Cochemiea s.l., as previously suggested by Vázquez- Sánchez et al (2013). Furthermore, the taxonomy of Mammillaria has historically been difficult due to large morphological variability, phenotypic plasticity, sympatric distribution of species, and suspected hybridization events.…”
Section: Introductionsupporting
confidence: 76%
“…In the molecular analysis, Mammillaria sphacelata and M. benecki were recovered, with low support, as the sister group to Coryphantha s.s. In contrast, Breslin et al (2021) found M. sphacelata to be the sister to Escobaria + Coryphantha . The addition of eight morphological characters in the combined analysis recovered M. sphacelata and M. beneckei within the clade Mammillaria , and supported Coryphantha s.s. and Escobaria as sister lineages.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, Breslin et al (2021) proposed Escobaria and Coryphantha to be a single genus, as traditionally treated by North American botanists ( Benson 1982 ; Zimmerman and Parfitt 2004 ). However, sampling in Mexican Coryphantha was not representative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is nonmonophyletic (Butterworth and Wallace, 2004), and recently it was also proposed that the Mammiloid clade circumscribes three monophyletic genera: Mammillaria s.s., Coryphantha and Cochemiea s.l. (Breslin et al, 2021). The Mammilloid clade is estimated to have diverged for the last 8.62 million years (Hernández-Hernández et al, 2014).…”
Section: Introductionmentioning
confidence: 99%